Stable isotope geochemistry related 10 gold mineralization and expwration in the western shield - T. Kurtis Kyser; Brian W. Janser; Mark R. Wilson; Ian Hattie (Canadian Institute of Mining, Metallurgy and Petroleum, 1986)
Petrographic, chemical and isotopic compo itions of auriferous and non-auriferous quartz vei ns from the Sta r Lake and Flin Flin-Amisk Lake areas of northern Saskatchewan indicate diver e origins fo r the fluids associated with gold mineralization. In the Sta r Lake area, the metavolcanic , Star Lake pl uton, and heared mafic dikes have retained their original igneous 81 80 values. The 81 80 value of quartz from mi neralized veins vary by I per mi! and range from+I0 to+IJ. The only quartz ample having a 81 80 value outside th is range came from a vein not associated wi th a dike or gold mineralization . Quartz from the Star Lake pluton has identical 8180 value to the qua rtz from mi neralized vei ns which suggests that the vei ns and the pluton are related to imilar proces es. The diffe rence in 81 80 values between mi neralized and barren vein may erve a a potential exploration tool in this area. Because o34S val ues of a limi ted number of amples of pyrite from gold-bearing quartz vei ns at Star Lake correlate directly with gold content. the gold may have been syngenetic with the su lphur and the 834 value may be useful for exploration . 8180 values of co-existing quartz, calcite, and amphibole in the veins from Star Lake indicate that isotopic disequilibrium among the minerals is common, but the val ues also record a high temperature of formation (ea . 500°C) involvi ng a component of magmatic fl uid. TheoD value of hydrou mineral from Star Lake retain their original igneous values but whole rock values are generally much lower, an effect attributed to interaction of the minerals with a late meteoric water. In the Fl in Flin-Amisk Lake area, auriferou and barren quartz veins formed from a mixture of hydrothermal and metamorph ic flu id at lower temperatures (ea . 350°C) than those at Sta r Lake. Becau e there i no apparent correlation between 8180 values of the quartz with gold content or relative age of the vein , nor between the 834S val ues of pyrite and gold content, table isotopes appear limited as an exploration tool in the Fl in FlonAmisk Lake areas.